Addiction and reward-related genes show altered expression in the postpartum nucleus accumbens - Zhao, Changjiu; Eisinger, Brian Earl; Driessen, Terri M.; Gammie, Stephen C. (Frontiers in Behavioral Neuroscience, 2014)
Motherhood involves a switch in natural rewards, whereby offspring become highly rewarding. Nucleus accumbens (NAC) is a key CNS region for natural rewards and addictions, but to date no study has evaluated on a large scale the events in NAC that underlie the maternal change in natural rewards. In this study we utilized microarray and bioinformatics approaches to evaluate postpartum NAC gene expression changes in mice. Modular Single-set Enrichment Test (MSET) indicated that postpartum (relative to virgin) NAC gene expression profile was significantly enriched for genes related to addiction and reward in 5 of 5 independently curated databases (e.g., Malacards, Phenopedia). Over 100 addiction/reward related genes were identified and these included: Per1, Per2, Arc, Homer2, Creb1, Grm3, Fosb, Gabrb3, Adra2a, Ntrk2, Cry1, Penk, Cartpt, Adcy1, Npy1r, Htr1a, Drd1a, Gria1, and Pdyn. ToppCluster analysis found maternal NAC expression profile to be significantly enriched for genes related to the drug action of nicotine, ketamine, and dronabinol. Pathway analysis indicated postpartum NAC as enriched for RNA processing, CNS development/differentiation, and transcriptional regulation. Weighted Gene Coexpression Network Analysis identified possible networks for transcription factors, including Nr1d1, Per2, Fosb, Egr1, and Nr4a1. The postpartum state involves increased risk for mental health disorders and MSET analysis indicated postpartum NAC to be enriched for genes related to depression, bipolar disorder, and schizophrenia. Mental health related genes included: Fabp7, Grm3, Penk, and Nr1d1. We confirmed via quantitative PCR Nr1d1, Per2, Grm3, Penk, Drd1a, and Pdyn. This study indicates for the first time that postpartum NAC involves large scale gene expression alterations linked to addiction and reward. Because the postpartum state also involves decreased response to drugs, the findings could provide insights into how to mitigate addictions.